If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + 6 + -7n = 19 Reorder the terms: 6 + -3n + -7n = 19 Combine like terms: -3n + -7n = -10n 6 + -10n = 19 Solving 6 + -10n = 19 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -10n = 19 + -6 Combine like terms: 6 + -6 = 0 0 + -10n = 19 + -6 -10n = 19 + -6 Combine like terms: 19 + -6 = 13 -10n = 13 Divide each side by '-10'. n = -1.3 Simplifying n = -1.3
| x^2-12=20 | | 12+9(3z-2)-15z= | | 2(2X+3)(X-5)=0 | | -2x+5-x=17 | | (x+1)(x+1)=2(x+1) | | -16=d+12 | | 16+x=43 | | 1(2X+3)(X-5)=0 | | 0(2X+3)(X-5)=0 | | x^2-1.6x=0 | | 4(m+3)=2m+12 | | (2b-4)(3b+6)=0 | | 1.5+x=1725 | | -1(2X+3)(X-5)=0 | | 2x=8x-9 | | -3+4x=37 | | 0.5(5-2h)=h/2 | | 5t+1=-2t-6 | | 6=4-2k | | -5x+6=-34 | | 4x-2=6x+6 | | 88=4+7x | | 23x+90=24 | | 5x^2+3=x^2+51 | | 6+4y=11 | | N+12=2n+8 | | 5x+(3x+3)= | | 7y+6+64+4y=180 | | 12x^2+80x-28=0 | | 1+2x=99 | | 4(-x-1.6)=-4+6.4 | | x+3y-13=0 |